Leproide canine granulomatous syndrome - Coelho, P. T.; Rosa, A. C.; Cruz, G. D. (Scientific Electronic Archives, 2016)
<span style="font-family: 'Arial',sans-serif; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">The granulomatous lepróide syndrome and feline leprosy is a disease caused by mycobacteria without identification, due to the great difficulty of cultivation. Few are diagnosed in Brazil, but are relatively common. Cause nodular lesions, granulomatous which can be located in small areas, or spread throughout the body of the animal. Large dogs and the short is more likely, as well as wild cats or free-living pets. Diagnosis is cytological, histological and PCR. The treatment is varied according to the severity and extent of the lesions. Among the most commonly used drugs are rifanpicine, amikacin, enrofloxacin, ciprofloxacin and others.